The Influence of Human Rights on Death Penalty in Indonesian - Sofiana Dwi Prastiwi; Danang Darmawan (UM Purwokerto Press, 2023)
Death penalty has the status of principal punishment, is a type of punishment that contains pros and cons. At the international level, this type of punishment is prohibited from being imposed on convicts. The United Nations (UN) pushed for the abolition of this type of crime based on the Declaration of Human Rights which was adopted on December 10, 1948, by guaranteeing the right to life and protection against torture. This step was taken considering that the application of death penalty is contrary to human rights. Criminal execution by shooting the convict to death and not carried out in public. Imposition of capital punishment means taking away someone's right to life. Everyone has the right to live and has the right to defend his life and existence (Article 28A of the 1945 Constitution). Even the death penalty is no longer in harmony with the development of human rights. All countries have the concept of upholding human rights, Indonesia as part of the countries in the world participates in realizing human rights, it is proven that human rights are regulated legally and formally. Human rights, especially the right to life, are stated as rights that cannot be reduced in any form. However, in a positive way, the application of the death penalty is still mostly decided by judges. The purpose of this writing is to examine how human rights influence death penalty in Indonesia, using normative law research methods, namely research based on positive law studies. This study uses primary legal material in the form of laws and regulations, as the object of research. The law that is the object of research is the 1945 Constitution of the Republic of Indonesia which is related to human rights. In conclusion, human rights are rights related to the nature of human existence. Criminal imposition of convicted criminals must be oriented towards the protection of human rights